Truncal Vagotomy and Drainage for Chronic Duodenal Ulcer Disease: A Controlled Trial. Issue 5858 (14th April 1973) - Kennedy, F.; MacKay, C.; Bedi, B. S.; Kay, A. W.
Abstract : The results of elective truncal vagotomy and drainage in 547 duodenal ulcer patients are reported. Altogether, 204 patients were randomly allocated to pyloroplasty and 200 to gastrojejunostomy. In 101 patients gastrojejunostomy was electively chosen and in 42 patients the duodenum was opened to confirm the diagnosis. Operative mortality was 0·5%, the incidence of proved recurrent ulceration 3·3%, severe dumping 2%, and severe diarrhoea 1·1%. There were no significant differences between the groups, with the exception of bilious vomiting which occurred more often in patients with gastrojejunostomy.